The Foreign Investment in Oil Sector in Iraq after 2003 (Journal of the College of Education for Women, 2019)
Iraq has the distinction of being a great potential of non-renewable natural resources,especially crude oil and natural gas. Since the discovery of crude oil at the beginning of thetwentieth century in Iraq. Although the different of investment types, it contributed to the oilsector in the provision of financial resources to the state treasury , since that date until thepresent time.Search has been marked by division ((The foreign investment in the oil sector in Iraq after2003)) into three sections. The first section included a brief history of the development ofIraq's oil potential in terms of oil reserves, and oil fields, and the quantities of production andexport. The second section reviewed the investment policies in the oil sector after 2003, thefoundations have been dealt with legislative and practical applications and signing investmentcontracts after four licensing rounds. The third section, focused on the challenges of investingin the oil sector in Iraq, such as strictly intellectual challenge, economic problems, legalobstacles, security constraints and political differences . The search is over and ended byconclusions.